1-m+7-6+10m=

Simple and best practice solution for 1-m+7-6+10m= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 1-m+7-6+10m= equation:


Simplifying
1 + -1m + 7 + -6 + 10m = 0

Reorder the terms:
1 + 7 + -6 + -1m + 10m = 0

Combine like terms: 1 + 7 = 8
8 + -6 + -1m + 10m = 0

Combine like terms: 8 + -6 = 2
2 + -1m + 10m = 0

Combine like terms: -1m + 10m = 9m
2 + 9m = 0

Solving
2 + 9m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 9m = 0 + -2

Combine like terms: 2 + -2 = 0
0 + 9m = 0 + -2
9m = 0 + -2

Combine like terms: 0 + -2 = -2
9m = -2

Divide each side by '9'.
m = -0.2222222222

Simplifying
m = -0.2222222222

See similar equations:

| 4m=-17 | | -81-9x=139+x | | 2x-3y+21=0 | | 5x+14=-17 | | -8x+5=28 | | X=100(.2x) | | 11j+4= | | -11(y+3)+5(3y-6)=3(y-3)+13 | | 11x+4-5x=21+7x-3 | | A(x)=x+6x+13 | | 3+21x+14x+12+40=180 | | -2(x-3)=-4x+20 | | X=100+(.2*x) | | lnx+4=1 | | 12x+6-(3x-5)=79 | | -6x=798 | | 32-17+2z=13 | | 8=-1+x | | 3x+11=4X-21 | | 4x+x-5=20 | | 2(x+1)1-4=12 | | 100=x(.02) | | k+-263.48=-381.09 | | 3y-15-8x-16=-2y-22 | | 5b+10=70 | | 7+9p=-110 | | -6x+4=10+8x | | 11x^2=13x+0 | | 40d^2+30=-14d^2 | | 100=x(.20) | | z=dxy | | (4x-6)3.5=119 |

Equations solver categories